Identity Struggles of Museum Professionals: Autonomous Expertise and Audience Participation in Exhibition Production - Taavi Tatsi (Journal of Ethnology and Folkloristics)
The established identity of a museum professional is that of a traditional modernist cultural expert, deploying hegemonic power stemming from institutionalised legitimate knowledge. At the same time, its identity work bastions its components against diverse forms of structural audience participation. The museum professional's identity responds to the challenge of structural audience participation with resistance, anxiety and othering. The museum professional's identity work involves a considerable amount of bastioning in that regard, and after participatory intervention has taken place, it works towards marking clearer frontiers between the legitimate expert and idealised amateur. With the experience, a small amount of assimilation of participatory diversification also appears, while the possibilities remain of a 'third expertise' emerging through future collaborative processes.